Emotion, proficiency, and arousal: exploring speech and physiological responses in Chinese ESL learners - Wu, Mengjiao; Roche, Jennifer M. (Frontiers in Human Neuroscience, 2025)
IntroductionThe coordination and expression of cultural specific affective cues during speech production in a second language (L2) reflects pragmatic adaptation, which is a critical step toward learning and achieving broader pragmatic competence. Embodied cognition provides a framework for understanding how cognitive and emotional processes shape L2 expression.ObjectiveThis study examined how immersive language experience influences pragmatic adaptation through the vocal expression of affect and physiological arousal in Chinese ESL learners.MethodsAcoustic analysis and electrodermal activity (EDA) measurements were used to assess affectively valenced word production in speakers with varying levels of immersive English experience.ResultsHigh-immersion speakers exhibited greater pitch, intensity, and duration variation, enhancing emotional expressivity. Low-immersion speakers showed constrained vocal patterns and significantly higher physiological arousal, likely due to increased cognitive demands and anxiety.DiscussionThese findings highlight the impact of L2 proficiency on affective language embodiment and the cognitive challenges faced by L2 learners. This study offers novel insights by considering a pictorial character-based language, broadening our understanding of emotion-language interaction. Findings have implications for second-language education, cross-cultural communication, and bilingual speech therapy.